Find all functions \(f: \mathbb R \to \mathbb R \) such that for arbitrary real numbers \(x\) and \(y\),

\[ f(x+y) + f(x) f(y) = f(xy) + f(x) + f(y) .\]

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestPut \(x=y=0\) \[f(0)+f(0)^{2}=3f(0)\] This implies \(f(0)=0\) or \(f(0)=2\).

CaseI: \(f(0)=2\) Now put \(x=0\) \[3f(y)=4+f(y)\] \[\boxed{f(y)=2}\]Case II: \(f(0)=0\) Put \(x=y=2\) \[f(4)+f(2)^{2}=f(4)+2f(2)\] \(f(2)=2\) or \(f(2)=0\).Since the main functional equation all terms are only monic functions so another solution is \(f(y)=0\).

Other solution is \(f(y)=y\) which can be proved by induction.

Log in to reply

As mentioned by Ivan, I don't understand what you are doing here. I agree up the Case 2, but fail to follow form "Since the main functional equation ..."

Log in to reply

I mean that both sides have terms which have 1 as coefficient so each term can be zero.

Log in to reply

Yea Ivan has a point. I don't understand how u can use induction when the domain is reals ?

Log in to reply

The induction part is wrong, but it's a minor mistake; verifying that \(f(x) = x\) works is simply plugging it into the equation. The problem is that other potential solutions haven't been ruled out.

Log in to reply

You haven't shown that there is no other solution. In fact, as my solution suggests, if we restrict \(f\) only to the integers, there exists another solution, and you haven't ruled it out.

Log in to reply

Let \(P(x,y)\) be the statement \(f(x+y) + f(x)f(y) = f(xy) + f(x) + f(y)\).

\(P(x,0) \implies f(x) + f(x)f(0) = f(0) + f(x) + f(0) \implies f(x)f(0) = 2f(0)\). If \(f(0) \neq 0\), we can cancel it to give \(f(x) = 2\) for all \(x\), which is a solution. Otherwise, \(f(0) = 0\).

\(P(2,2) \implies f(4) + f(2)f(2) = f(4) + f(2) + f(2) \implies f(2)^2 = 2f(2)\). This gives \(f(2) = 0\) or \(f(2) = 2\).

\(P(1,1) \implies f(2) + f(1)^2 = 3f(1)\). If \(f(2) = 0\), this leads to \(f(1) = 0\) or \(f(1) = 3\). If \(f(2) = 2\), this leads to \(f(1) = 1\) or \(f(1) = 2\).

\(P(-1,1) \implies f(-1)f(1) = 2f(-1) + f(1)\). \(f(1) = 2\) leads to a contradiction, so we are left with three cases. To recap, our current cases are \((f(1), f(2)) = (0,0), (1,2), (3,0)\).

\(P(x,1) \implies f(x+1) + f(x)f(1) = 2f(x) + f(1)\). We can now apply induction (in both ways, going on the positive integers and the negative integers) to determine the value of \(f\) on the integers:

Case 1:\(f(1) = 0,\). Then \(P(x,1) \implies f(x+1) = 2f(x)\). Inducting gives \(f(x) = 0\) for all integer \(x\).Case 2:\(f(1) = 1\). Then \(P(x,1) \implies f(x+1) = f(x) + 1\). Inducting gives \(f(x) = x\) for all integer \(x\).Case 3:\(f(1) = 3\). Then \(P(x,1) \implies f(x+1) = 3 - f(x)\). Inducting gives \(f(x) = 3\) if \(x\) is odd and \(f(x) = 0\) if \(x\) is even.Let \(x = \frac{p+1}{p}, y = p+1\) for nonzero integer \(p\). Note that \(x+y = xy\). Thus \(P(x,y) \implies f(x)f(y) = f(x) + f(y)\). Since we know the value of \(f(y)\), we can determine the value of \(f(x)\). That is, the value of \(f \left( 1 + \frac{p}{1} \right)\).

Using \(P(x,1)\), we can induct again to determine the values of \(f \left( n + \frac{1}{p} \right)\) for all integer \(n\), including \(n = 0\).

\(P \left( \frac{1}{p}, n \right) \implies f \left( \frac{n}{p} \right) + f \left( \frac{1}{p} \right) f(n) = f \left( n + \frac{1}{p} \right) + f \left( \frac{1}{p} \right) + f(n)\). Since we know the values of \(f \left( \frac{1}{p} \right)\), \(f \left( n + \frac{1}{p} \right)\), and \(f(n)\), we know the value of \(f \left( \frac{n}{p} \right)\). That is, we know \(f\) to the rationals. I haven't actually worked it out to figure out whether Case 3 still persists.

I'm not sure how to extend this to the reals. I'm also pretty sure this is too convoluted (that is, there should be a simpler solution). You might want to first try to solve the following: find all \(f\) on the reals such that \(f(x+y) = f(x) + f(y)\) and \(f(xy) = f(x)f(y)\) for all reals \(x,y\).

Log in to reply

I believe that you're missing the constant solution \( f(x) = 2 \).

Log in to reply

I already wrote that one near the top.

Log in to reply

Can u too please post some functional equations to solve ? I am quite weak at that

Log in to reply

Try these:

\(1\). If \(f\) is a polynomial function satisying \(2+f(x)f(y)=f(x)+f(y)+f(xy)\) for all real \(x,y\) and if \(f(2)=5\), find \(f(f(2))\).

\(2\). A polynomial function \(f(x)\) satisfies the condition \(f(x)f(\dfrac{1}{x})=f(x)+f(\dfrac{1}{x})\) if \(f(12)=1729\), then find \(f(10)\).

\(3\).Find all functions \(f\) from \(R{0,1}\) to \(R\) satisfying the functional relation \(f(x)+f(\dfrac{1}{1-x})=\dfrac{2(1-2x)}{x(1-x)}\). Source:INMO

Buy the book Functional Equations by B.J. Venkatachala. It has very nice functional equations problem .

Log in to reply

Hey should we make a thread for "Brilliant Functional Equation Contest" ? This is just an excuse for me to improve our functional equation as one problem in INMO is definitely on functional equations.

Log in to reply

A functional equation problem shouldn't have the statement "if \(f\) is a polynomial..."; that statement makes it a polynomial equation problem (which has quite a different method to solve them).

Log in to reply